Tiga Prinsip Tasawuf dalam Surah Al-Fatihah: Kajian Atas Tafsir Al-Barru Karya Muhammad Rusli Malik - Ahmed Zaranggi Ar Ridho (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2021)
This article aims to analyze the influence of Sufism in the interpretation of the Qur'an in Eastern Indonesia through Muhammad Rusli Malik's tafsir entitled Al-Barru. This article uses Hans Gadamer's hermeneutic approach which focuses on two things; first, the history of Rusli Malik's influence with Sufism, second, tracing the influence of the interpretation of Surah Al-Fatihah Rusli Malik with the teachings of Sufism. As a result, Rusli Malik's background and life journey in the Muhammadiyyah and Jamaah Tabligh organizations have a connection with the emergence of three main principles of Sufism, namely the principle of self-purification (tazkiyyatun nafs), the principle of God's manifestation (tajallī illāhī) and the unity of being (waḥdatul wujūd) in his interpretation. All three indicate that the tradition of Sufism in the Sulawesi region sublimates in various lines of community organizations, including Muhammadiyah and Jamaah Tabligh.